2020
DOI: 10.1109/access.2020.3000606
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy-Theory-Based Cellular Automata Model for Pedestrian Evacuation From a Multiple-Exit Room

Abstract: The exit selection behavior of pedestrians plays an important part in the process of evacuation. This paper proposes a cellular automata model based on fuzzy logic method for simulating the evacuation of pedestrians from a multiple-exit room. When pedestrians select the exit, the distance and density are adopted as two important input variables in the fuzzy logic method, and the probability of selecting each exit is defined as the output variable of fuzzy logic method. The output variable of fuzzy logic, exit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…For example, Yang et al utilized fuzzy logic to model exit selection using two input parameters: Normalized distance and normalized density [37]. Liu et al followed a similar approach like Yang et al However, they combined the output of the fuzzy logic system with exit width and herding behavior to determine the target exit [38]. Their research demonstrated that the modified multinomial logit model with revising decisions outperforms the other two models [43].…”
Section: Related Workmentioning
confidence: 99%
“…For example, Yang et al utilized fuzzy logic to model exit selection using two input parameters: Normalized distance and normalized density [37]. Liu et al followed a similar approach like Yang et al However, they combined the output of the fuzzy logic system with exit width and herding behavior to determine the target exit [38]. Their research demonstrated that the modified multinomial logit model with revising decisions outperforms the other two models [43].…”
Section: Related Workmentioning
confidence: 99%
“…There are two categories for pedestrian evacuation research, i.e., empirical methods [1][2][3][4][5][6][7][8][9][10][11][12][13] and simulation methods [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The results of the experiments can provide the basic data for the prediction of pedestrian evacuation.…”
Section: Introductionmentioning
confidence: 99%
“…In the simulation process of microscopic model, each pedestrian is regarded as a discrete individual. Typical representatives of the microscopic model are the social force, lattice gas, and cellular automaton models [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In the social force model, the pedestrians can be considered as structureless particles and the movement is based on Newtonian mechanics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the occurred emergency events (such as fire, earthquake, and terrorist attacks), since the pedestrians in the evacuation space are usually myopic and many irrational behaviors may inherently and negatively affect the pedestrians' decision making (which may eventually lead to an efficiency loss causing huge casualties) in the evacuation process [1][2][3][4], some evacuation strategies are often beforehand designed to enhance the evacuation efficiency. In the literature, those evacuation strategies include the choices on room layout [5], number of exits [6], location of obstacles [7], to name but a few. To effectively evaluate the evacuation efficiency, establishing mathematical models describing the pedestrians' decision making behaviors and the resulting phenomena in the evacuation process should be of prime importance [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%